Truncation error estimation for Newton–Cotes quadrature formulas - Plukas, Kostas; Plukienė, Danutė (Lietuvos matematikos rinkinys, 2004)
Theoretical and practical aspects of truncation error estimation for Newton–Cotes quadrature formulas are discussed in this paper.